A molecular network-based pharmacological study on the protective effect of Panax notoginseng rhizomes against renal ischemia–reperfusion injury - Li, Dan-Dan; Li, Na; Cai, Chui; Wei, Chun-Mian; Liu, Guang-Hua; Wang, Ting-Hua; Xu, Fu-Rong (Frontiers in Pharmacology, 2023)
Objective: To explore the protective effect of Panax notoginseng rhizomes (PNR) on Renal ischemia and reperfusion injury (RIRI) and the underlying molecular network mechanism based on network pharmacology, combined systemic experimental validation. Methods: A bilateral RIRI model was established, and Cr, SCr, and BUN levels were detected. Then, the PNR was pretreated one week before the RIRI model was prepared. To determine the effects of PNR in RIRI, histopathological damage and the effect of PNR to the kidney was assessed, using TTC, HE, and TUNEL staining. Furthermore, the underlying network pharmacology mechanism was detected by screening drug-disease intersection targets from PPI protein interactions, GO and KEGG analysis, and the hub genes were screened for molecular docking based on the Degree value. Finally, the expression of hub genes in kidney tissues was verified by qPCR, and the protein expression of related genes was further detected by WB. Results: PNR pretreatment could effectively increase Cr level, decrease SCr and BUN levels, reduce renal infarct areas and renal tubular cell injury areas, and inhibite renal cell apoptosis. By using network pharmacology combined with bioinformatics, we screened co-targets both Panax notoginseng (Sanchi) and RIRI, 10 hub genes were acquired, and successfully performed molecular docking. Of these, pretreatment with PNR reduced the mRNA levels of IL6 and MMP9 at 1 day postoperatively and TP53 at 7 days postoperatively, and the protein expression of MMP9 at 1 day postoperatively in IRI rats. These results showed that PNR could decrease kidney pathological injury in IRI rats, inhibite apoptotic reaction and cell inflammation, so as to improve effectively renal injury, and the core network mechanism is involved in the inhibition ofMMP9, TP53 and IL6. Conclusions: PNR has a marked protective effect for RIRI, and the underlying mechanism is involved in inhibiting the expression of MMP9, TP53 and IL6. These striking discovery is not only provide the fruitful evidence for the protective effect of PNR in RIRI rats, but also provide a novel mechanic explaination.